Hall effect studies in YBCO films - Solovjov, A.L. (Физика низких температур, 1998)
The longitudinal, rhoxx(T), transverse, rhoxy(T), and Hall, rhoH(T) resistivities have been measured for YBa₂Cu₃Ox (YBCO) films, showing positive resistivity buckling and those with usual linear rhoxx(T) dependence. In the former case unexpected peak on rhoxy(T) and unusual rhoH(T) dependence with double sign change just above transition temperature Tc have been revealed. The data are analyzed using recent theory for the sign of the Hall conductivity in strongly correlated systems.